2013
DOI: 10.4049/jimmunol.1203518
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania-Infected MHC Class IIhigh Dendritic Cells Polarize CD4+ T Cells toward a Nonprotective T-bet+ IFN-γ+ IL-10+ Phenotype

Abstract: A differential behavior among infected and bystander dendritic cells (DCs) has been explored in different infection models. We have analyzed both populations sorted on contact with visceral Leishmania infantum on a susceptible mice model evaluating the subsequent repercussions on adaptive immune response. Our results demonstrate a clear dichotomy between the immunomodulatory abilities of bystander and infected DCs. The bystander population presents increased levels of IL-12p40 and costimulatory molecules being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
7
27
0
Order By: Relevance
“…Leishmania infection induced lower amounts of IL-12p40 production compared to amounts observed when cells were stimulated with only LPS (Figure 3A), which is consistent with previous research [36]. Interestingly, the production of IL-12p40 was decreased mainly in BOS1FL1- and POL2FL7-infected BMMø and BMDC ( P <0.05), compared to amounts observed during infection with the BCN150 strain (Figure 3A).…”
Section: Resultssupporting
confidence: 91%
“…Leishmania infection induced lower amounts of IL-12p40 production compared to amounts observed when cells were stimulated with only LPS (Figure 3A), which is consistent with previous research [36]. Interestingly, the production of IL-12p40 was decreased mainly in BOS1FL1- and POL2FL7-infected BMMø and BMDC ( P <0.05), compared to amounts observed during infection with the BCN150 strain (Figure 3A).…”
Section: Resultssupporting
confidence: 91%
“…Silent infection is a main feature of Leishmania strains causing nonhealing forms of the disease, since defects in DCs maturation may, in part, contribute to the unpolarized T cell phenotype occurring during these Leishmania infections. It is quite possible that a decline of IL-12/IL-IO ratio creates a microenviroment that aberrantly favours parasite establishment, since IL-IO enhances VL establishment by suppressing Th 1 cell activation and proliferation through the generation of Treg (24). Similarly, we showed that L. irifantum-infected BM-DCs produced significant levels of TNF-u and IL-I O.…”
Section: Inhib Ition Oferki/2 Activation Up-regulates Il-1 2/ Il-io Rsupporting
confidence: 62%
“…These cells were characterized as high-level CD40 expressing DCs after L. major uptake (15). However, in our study only infected cells were characterized by (24,26). Silent infection is a main feature of Leishmania strains causing nonhealing forms of the disease, since defects in DCs maturation may, in part, contribute to the unpolarized T cell phenotype occurring during these Leishmania infections.…”
Section: Inhib Ition Oferki/2 Activation Up-regulates Il-1 2/ Il-io Rmentioning
confidence: 77%
“…Pkm2 transcription has been related with macrophage [20,21] and NF-kB activation [22]. This phenomenon suggests that bystander macrophages could be activated in a similar fashion as it was demonstrated to occur with bystander dendritic cells [23,24] or even by infected macrophage secreted extracellular vesicles [25]. From the early energetic and metabolic settings responsible for a glycolytic environment resulted a nutrient and energetic deficit.…”
Section: Discussionmentioning
confidence: 94%